A companion to the Latin medieval commentaries on Aristotle's Metaphysics - Amerini, Fabrizio (Brill's companions to the Christian tradition ;, 2013)
Few philosophical books have been so influential in the development of Western thought as Aristotle's Metaphysics. In fourteen substantial essays this volume reconstructs the late medieval reception of this work, by focusing on the main medieval commentators and a common set of metaphysical topics.